On the problem of territorial distribution of sample areas for landscape monitoring purposes - Jankauskaitė, Margarita; Veteikis, Darijus (Journal of Environmental Engineering and Landscape Management, 2010)
Today landscape change monitoring becomes important in the field of sustainable development planning. Real changes of landscape have to be observed in a large scale (not smaller than 1:10,000) in order to avoid generalization of small landscape elements. In such a scale it is rational to perform the monitoring in sample areas that would be enough statistically abundant. The paper offers an original method of distributing the landscape sample areas in Lithuanian territory, differing from most methods based on random choose of sample areas though thorough analysis of the analogous methods abroad was performed. The work was sponsored by the Environmental Agency at the Lithuanian Ministry of Environment. In accordance to the spread of different natural landscape types (like clayey plains, morainic hills, sandy plains, etc.), a set of 100 sample areas (2.5 km2 each) was distributed in Lithuanian territory. To increase the sample area number in smaller landscape types (spit, coastal sandy plain, delta), some proportional corrections were made. Thus, the largest number of the sample areas was assigned to the most spread clayey plains (22), the smallest number – to sandy coastal plain (3). In order to find a concrete place for each sample area inside the landscape type a computer program was employed and the highest representation principle applied. Several tens of thousands possible positions of the sample areas were tested in order to find the best in representing land cover structure. This was achieved by calculating relative remoteness of tested samples’ land cover structure from the respective landscape type structure, further selecting the most patchy samples. Selecting the position of a sample area was also influenced by the buffer capacity (resistance to the chemical impact) of landscape, mostly concentrating on the areas with less buffer capacity (more sensitive to chemical pollution). Kraštovaizdžio stebėsenos vietos lygmeniu etalonų teritorinio išdėstymo problema Santrauka. Tvariajai plėtrai planuoti tampa aktualia kraštovaizdžio kaitos stebesėna. Realūs kraštovaizdžio pokyčiai Lietuvos mastu turi būti fiksuojami stambiuoju masteliu (ne smulkesniu nei 1:10 000), vengiant nepageidautino smulkių kraštovaizdžio elementų generalizavimo. Tokiu masteliu racionalu būtų pokyčių stebėjimus atlikti etalonuose, jų skaičius turėtų būti statistiškai patikimas. Pateikiama originali kraštovaizdžio monitoringo etalonų išdėstymo Lietuvos teritorijoje metodika. Darbas buvo atliktas remiant Aplinkos apsaugos agentūrai prie Lietuvos aplinkos ministerijos. Metodika parengta atsižvelgiant ir į užsienio šalių patirtį. Pagal kraštovaizdžio tipų paplitimą proporcingai buvo išdalyta 100 2,5 km2 ploto etalonų, papildomai koreguojant (padidinant) etalonų skaičių mažai paplitusiuose kraštovaizdžio tipuose (Nerijoje, pajūrio lygumoje, deltoje). Taigi daugiausia etalonų (22) buvo skirta plačiausiai paplitusioms molingosioms lygumoms, mažiausiai (3) – pajūrio lygumai. Etalonams konkrečios vietos buvo parenkamos kompiuterine programa ir vadovautasi didžiausio reprezentatyvumo principu. Kiekvieno kraštovaizdžio tipo buvo išbandyta nuo kelių šimtų iki keliasdešimties tūkstančių galimų etalonų padečiu, nustatyta pagal žemes dangos struktūrą reprezentuojančios geriausiai. Etalonų vietų parinkimas buvo siejamas ir su kraštovaizdžio buferiškumo cheminei taršai arealais, daugiau koncentruojant mažesnio buferiškumo (jautresniuose cheminei taršai) plotuose. Reikšminiai žodžiai: kraštovaizdžio monitoringas, stebėsenos etalonai, didžiausio atstovavimo principas, žemės dangos struktūra, gamtiniai kraštovaizdžio tipai. K вопросу о территориальном распределении эталонных ареалов для ландшафтного мониторинга местного уровня Резюме. В настоящее время мониторинг изменений ландшафта становится актуальным для планировки сбалансированного развития. Реальные изменения ландшафта в Литве должны быть прослеживаемы в крупном масштабе (не мельче чем 1:10.000) во избежание нежелательной генерализации мелких структурных элементов ландшафта. В таком масштабе рационально осуществлять наблюдения на специально выделенных эталонных территориях, число которых должно быть статистически достаточным. В статье приведена методика расположения названных эталонов на территории Литвы. Работа выполнена при поддержке Агентства по охране окружающей среды при Министерстве окружающей среды. Методика разработана с учетом опыта зарубежных стран. С учетом распределения ландшафтных типов пропорционально было поделено сто эталонов площадью 2,5 км2 каждый. Дополнительно корректировалось (увеличивалось) число эталонов в мало распространенных ландшафтных типах (на косе, приморской равнине, в дельте). Наибольшее число эталонов (22) было отдано глинистым (наиболее распространенным) равнинам, а наименьшее (3) – приморской равнине. С целью подбоpa для эталонов конкретных мест была применена компьютерная программа, а также следовали принципу наивысшей репрезентативности. В каждом ландшафтном типе было испробовано от нескольких сот до нескольких десятков тысяч возможных положений эталонов с целью определить лучшее положение по репрезентативности земельно покровной структуры. Подбор мест для эталонов был осуществлен с учетом сопротивляемости ландшафта химическому загрязнению. Больше эталонов размещалось в наименее устойчивых ареалах. Ключевые слова: мониторинг ландшафта, эталонные ареалы, принцип наивысшей репрезентативности, структура земельного покрова, природные типы ландшафта. First Publish Online: 10 Feb 2011